ROLE OF DIETARY INTAKE AS RISK FACTOR FOR NASOPHARYNGEAL CARCINOMA IN MUHAMMADIYAH HOSPITAL PALEMBANG JUNE 2017-SEPTEMBER 2018 - Norman Imansyah Rizal; Denny Satria Utama (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction Nasopharyngeal Carcinoma (NPC) are the most common malignancy of Ear, Nose, Throat, Head and Neck in Indonesia. Until now Epstein Barr virus as factor causing NPC, but nonviral cause like dietary intake and food can also cause an increase in the prevalence of NPC. Objective To evaluate the role of dietary intake as a risk factor in NPC patients in the department ORLHNS Muhammadiyah Hospital Palembang. Material and method Using medical record data in Muhammadiyah Hospital Palembang from June 2017 until September 2018, this is a descriptive crossectional study. The primary outcomes were patient medical history about their dietary intake, as well as examination for NPC like physical examination, CT Scan, and biopsy result. Result A total of 17 cases of NPC, 64.70% (11 patients) were man and 35.3% (6 patients) were women. From medical history we get dietary factor that as risk factor to cause NPC were salted fish 11 patient (64.7%), 4 salted meat (23.5%) and 2 alcohol consumption (5.9%). Conclusion Dietary intake or food are a non-viral factors that correlate in increasing the risk of NPC. The highest dietary factors are salted fish (64.7%).